Effects of Intervening Loan to Deposit Ratio on Profitability - Laynita Sari; Renil Septiano (Journal of Accounting and Finance Management, 2020)
Government banks have a higher level of trust in society, as most of these shares are owned by the Government. Ratio used to assess a bank’s performance is the Return on Asset ratio. Each bank will try to keep its Return on Asset ratio consistently rising and the Non Performing Loan ratio consistently falling. But the phenomenon is that the ratio of Return on Asset and Non Performing Loan at the Government Bank fluctuated from 2014 to 2019. I will therefore examine the factors that affect the ratio of Return on Assets and Non-Performing Loans to government banks. In this study, the ratios used were Non Performing Loan, Net Interest Margin, Capital Adequacy Ratio as an independent variable, Loan to Deposit Ratio as an intervening variable and Return on Asset on its dependent variables. The result that the Variable Loan to Deposit Ratio mediates the relationship between Net Interest Margin and Return on Asset.